Pecado, castigo e redenção em A Pena e a lei de Ariano Suassuna - Homem, Mayla Souza Cruz (2010)
The poetry, the musicality, the miths, the faith have always been insert in Ariano Suassuna´s life. These elements take part in his works. The purpose of this is study is to analise the religious aspects in the play A Pena e a Lei, how such characteristics are shown in the story, and if the characters are or are not punished. This analysis will begin with biblics elements study and among with the saints life. The main hypothesis is that Suassuna´s works are influenced by religious aspects, and, due to that his stories will always have a critical and moral aspect. This study is mainly established on the analysis of the third act of the play A Pena e a Lei. The focus of this study is to compare biblical texts, readings about demon´s history and popular literature. This study is divided into three chapters: writer´s life, orality researchs and an analysis of religious aspects. In the end, everything resumes in forgiveness and hope